Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1177/1077801295001002005
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Rape

Abstract: This study examines the magnitude and prevalence of fear of crime as a function of seriousness and probability of occurrence among Greek university students aged 17 to 29. The findings show that fear of rape is the greatest fear of almost all young Greek women, greater than the fear of other serious offenses such as murder. This finding is interpreted in light of rape's reported likelihood in conjunction with its reported seriousness. Further, the precautionary measures show an avoidance pattern in Greek women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Given that the comparisons involve similar levels of threatened or actual physical contact, we suggest that the sex-based nature of threats and/or physical contact inherent in SC and/or USA-physical (as opposed to the generalized nature of WA) account for these findings. Further, drawing on previous research exploring the "fear of rape" (e.g., Gordon & Riger, 1991;Softas-Nall et al, 1995;Warr, 1985), it is also plausible that, given the type of threats to bodily integrity posed by sexualized forms of mistreatment, such behavior may evoke female fears of more serious sexual abuse and penetrative assault (Warr & Stafford, 1983). SC and USA-physical may thus exert greater negative effects on well-being than more generalized forms of aggression by increasing the perceived likelihood, and thus fear, of being raped, though empirical validation is required to make such a conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the comparisons involve similar levels of threatened or actual physical contact, we suggest that the sex-based nature of threats and/or physical contact inherent in SC and/or USA-physical (as opposed to the generalized nature of WA) account for these findings. Further, drawing on previous research exploring the "fear of rape" (e.g., Gordon & Riger, 1991;Softas-Nall et al, 1995;Warr, 1985), it is also plausible that, given the type of threats to bodily integrity posed by sexualized forms of mistreatment, such behavior may evoke female fears of more serious sexual abuse and penetrative assault (Warr & Stafford, 1983). SC and USA-physical may thus exert greater negative effects on well-being than more generalized forms of aggression by increasing the perceived likelihood, and thus fear, of being raped, though empirical validation is required to make such a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as gender represents a social group from which one cannot easily decouple, identity-based victimization is likely to be seen as more unavoidable and hopeless, when compared with forms of aggression that are not tied to an immutable characteristic. Indeed, sexual victimization is a pervasive fear among most women, and seen by many as an unavoidable risk associated with being female (e.g., Gordon & Riger, 1991;Softas-Nall, Bardos, & Fakinos, 1995;Warr, 1985). Paradoxically, while the connection to an identifiable trait renders SH illegal, thus making it a form of mistreatment from which targets can receive protection, victims of SH typically do not access legal defenses.…”
Section: Comparing Sexual Harassment and Workplace Aggressionmentioning
confidence: 99%
“…From that point forward research on fear of rape quickly shifted to college campuses and students. Softas-Nall et al (1995) found that fear of rape was prevalent among female students in Greece. Female students viewed rape as more serious than male students and were more likely to modify their lives to protect themselves.…”
Section: Introductionmentioning
confidence: 99%
“…por Day, 1994, e no estudo realizado por SoftasNall e col. (1995) este medo chega a ultrapassar qualquer tipo de ofensa, inclusive o homicídio. A violação é o crime que as mulheres temem mais do que os homens, pois consideram-no mais sério que os homens, e percepcionam um maior risco de vitimação deste crime em relação aos homens (Softas-Nall et al, 1995). Crê-se que uma fonte de medo é, efectivamente, o carácter sexual inerente a este crime (Day, 1994).…”
unclassified
“…por Softas-Nall, 1995), Canadá (Gomme, 1986, cit. por Softas-Nall, 1995 e Grécia (Softas-Nall et al, 1995).…”
unclassified